Long-term outcomes of COVID-19 intensive care unit survivors and their family members: a one year follow-up prospective study - Laurent, Raphael; Correia, Patricia; Lachand, Raphael; Diconne, Eric; Ezingeard, Eric; Bruna, Franklin; Guenier, Pierre-Alban; Page, Dominique; Périnel-Ragey, Sophie; Thiéry, Guillaume (Frontiers in Public Health, 2023)
To describe the long-term physical, functional and mental status of COVID-19 intensive care unit (ICU) patients and their family members one year after ICU discharge.We performed a prospective observational cohort study among patients admitted to the ICU for COVID-19-associated respiratory failure and their family members. Patients attended a one-year follow-up consultation with family members. Physical, functional and respiratory outcomes were collected. In addition, participants completed the Hospital Anxiety and Depression Scale and the Revised Impact of Event Scale. Qualitative components were collected during a 2-hour face-to-face interview.Fifty-four patients and 42 family members were included. Thirty-four (63%) patients reported chronic fatigue and 37 (68.5%) dyspnea. Computed tomography scans were abnormal in 34 patients (72.3%). Anxiety symptoms were present in 23 (48%) patients and 26 (66%) family members, depression in 11 (23%) and 13 (33%), and post-traumatic stress disorder in 12 (25%) and 23 (55%), respectively. Visit limitation was reported as the most painful experience for family members. Numerous patients recalled nightmares that contributed to the anxiety. Long-term reconstruction was difficult for both patients and family members.The vast majority of patients and their relatives reported long-term consequences on various physical and mental components, leading to a profound impact on their well being.